Seroprevalence of Ovine Enzootic Abortion of Sheep in Hama Governorate in Syria (Journal of Hama University, 2021)
312 blood samples were collected from 17 sheep flocks beyond to Awasi breed in the middle region in Hama governorate in the down town and provience to discover the seroprevalence of Ovine Enzootic Abortion of Sheep. The study involved 3715 sheep heads.The study was confirmed that the proportion of seroprevalence of abortion resulted of Chlamydia abortus reached to 11.53% as fraction 36/312 positive samples of specific antibodies of Chlamydia abortus. It was detected of positive antibodies of C. abortus in 5 study flocks with percent of 29.41%.The seroprevalence proportion of C. abortus in sheep study in Hama governorate ranged  between (0-100%) in tested samples from every flock, in which seroprevalence proportion reached 14.28% in down town, 16.66% in Koumhana, 33.33% in Tal-Altut, 33.33% in Al-Mbarkat, and the highest seropositive prevalence of C. abortus in Maarshoor 100%. However the tested samples from other study regions had been  negative of C. abourts.